Control systems engineering - Syed Najib Syed Salim (Penerbit Universiti Teknikal Malaysia Melaka, 2010)
Control system is a subject that should be learned by most people who are involved in engineering fields which includes electrical, mechanical and chemical, or any field that involves controlled processes. This book is suitable for students who are majoring in engineering fields especially in those three mentioned previously, either in the university, polytechnic or in any institutions that offers tha related fields.